1986
DOI: 10.1073/pnas.83.8.2614
|View full text |Cite
|
Sign up to set email alerts
|

The T11 glycoprotein is functionally linked to a calcium channel in precursor and mature T-lineage cells.

Abstract: Human T lymphocytes are activated through either the antigen/major histocompatibility complex receptor (T-Ti) Cells and Monoclonal Antibodies. Human T lymphocytes, T-cell clones, T11T3-natural killer clones (NK clones), and monoclonal antibodies anti-T3 IgM (2Ad2), anti-T3 .IgG2 (RW2-8C8), anti-T111, anti-T112, and antiT113 were produced and characterized as described (1, 2, 5-7). T3+ and T3-thymocytes were separated by rosette formation using 5% ox erythrocytes coated with anti-T3 monoclonal antibody and su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
40
1

Year Published

1987
1987
1998
1998

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(45 citation statements)
references
References 20 publications
(15 reference statements)
4
40
1
Order By: Relevance
“…CD2 expression under the conditions used. Retained CD2 expression is significant because some authors have suggested that T cell receptor/CD3 complex-mediated activation may be tied to the CD2 machinery (45).…”
Section: Resultsmentioning
confidence: 99%
“…CD2 expression under the conditions used. Retained CD2 expression is significant because some authors have suggested that T cell receptor/CD3 complex-mediated activation may be tied to the CD2 machinery (45).…”
Section: Resultsmentioning
confidence: 99%
“…T-cell activation by mitogens (41), antigens (42), or monoclonal antibodies against the T3/T-cell receptor protein complex (43) or the T11 glycoprotein (44) results in an increase in cytoplasmic free Ca2". This has led a number of groups to postulate the existence of at least a Ca2+ channel linked to the T11 structure and/or T3/T-cell receptor complex (40,44).…”
Section: Discussionmentioning
confidence: 99%
“…This appears as a low magnitude rise in Ca 2ϩ of short duration and most probably is due to the initial release of Ca 2ϩ from intracellular Ca 2ϩ stores ( Fig. 2A) (41,44,45).…”
Section: Cd2 Stimulation In the Absence Of P56 Lck Leads To A Prolongmentioning
confidence: 99%
“…In p56 lck expressing T cells, TCR stimulation is followed by an initial high transient Ca 2ϩ peak and a lower amplitude but sustained plateau phase (41,44,46). The initial rise of Ca 2ϩ is caused by the inositol trisphosphate-mediated release of Ca 2ϩ from the endoplasmatic reticulum (45) but is not sufficient for proliferation or IL-2 gene expression (41,71).…”
Section: Figmentioning
confidence: 99%